Pertanggungjawaban Pidana Korporasi terhadap Perkara Penyuapan kepada Pejabat Negara: Studi Putusan No. 23/PID.SUS-TPK/2022/PT.DKI - Fafirulloh, Monica Cecillila; Yulianingsih, Wiwin (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Corporations are legal entities that play a role in the economy and also have the potential to commit criminal offense, including corruption. Bribery commited by corporation constitutes corporate crime, which can harm the state, undermine integrity, and violate applicable law. One case of corporate crime that occurred was the corporate crime committed by PT Merial Esa. Decision No. 23/PID.SUS-TPK/2022/PT.DKI, PT Merial Esa was proven to have satisfied the subjective and objective elements of the crime of bribery. In this case, PT Merial Esa may be subject to legal consequences for the actions it takes. The research is grounded normative legal research. This research uses an legislative approach, which involves analyzing various relevant data sources, combined with a conceptual approach.